Peran Generasi Milenial Dalam Mengubah Lanskap Perilaku Organisasi - Galuh Prabowo; Muhammad Sidiq Purnomo (Jurnal Pendidikan Indonesia (JOUPI), 2024)
The millennial generation has a significant influence on organizational culture change. Organizations that want to succeed in the future need to adapt to the values ​​and expectations of this generation. By understanding and accommodating the needs of the millennial generation, organizations can create a more engaging, productive, and sustainable work environment. The influence of millennial values ​​on organizational culture is a dynamic and evolving process. By understanding the values ​​held by the millennial generation, organizations can create a more engaging, productive, and sustainable work environment. Based on the explanation above, this article aims to determine the influence of millennial values ​​on organizational culture. The method of writing this article is based on a qualitative approach with a literature review design which is also known as library research. Literature research is a research method that is carried out by collecting, analyzing, and interpreting information from various existing sources, such as scientific journals, books, articles, research reports, and other online sources. The results of this article indicate that the millennial generation is a valuable asset for organizations. By understanding their characteristics and expectations, organizations can create a more engaging and productive work environment. Organizations need to adapt to the changes brought by the millennial generation, such as Adjusting organizational values ​​to be more in line with the values ​​of the millennial generation, Providing appropriate training and development, Offering flexibility in working, Adopting a more collaborative leadership style.